PENGELOLAAN ZAKAT, INFAK, DAN SEDEKAH DALAM MENGENTASKAN KEMISKINAN DI MASA PANDEMI: (Studi di LAZISNU Kota Makassar Tahun 2020) - Ridwan; Darussalam; Alimuddin (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
The main problem of this research is the management of zakat, infaq, and alms in alleviating poverty in the pandemic period, study at LAZISNU Makassar City in 2020. The sub-problems are how is the management system of zakat, infaq, and alms at LAZISNU in alleviating poverty in Makassar City, and what are the obstacles or obstacles for LAZISNU in the management of zakat, infaq, and alms. The method used in this study is a qualitative method with a syar'i, social, and juridical normative approach. The results of this study indicate that in compiling the ZIS fund management program carried out by LAZIZNU Makassar City is good enough, to reduce the suffering of the poor, it affects the poverty rate to be reduced. However, there are obstacles that hinder management, one of which is the spread of Covid-19. Keywords: ZIS Management, Poverty, Pandemic Periode.